Anti-CNS antibodies in neurological and psychiatric disorders. Issue 11 (November 1987) - Plioplys, A V; Thibault, J; Bouchard, J P; Cockburn, C; Hawkes, R
Abstract : To investigate the possibility that anti-CNS antibodies may play a pathogenic role in a number of neurological and psychiatric disorders, a population study was undertaken. Serum samples were obtained from a total of 257 adults and were screened against sodium dodecyl sulphate polyacrylamide gel electrophoretic blots of various normal, necropsy-derived adult human brain regions. The incidence of IgG immunoreactive banding in the total sample was 30%. Within the diagnostic groups the incidence of banding was: controls 32%, schizophrenia 28%, mental retardation 27%, cerebellar ataxia 33%, Parkinson's disease 22%, myasthenia gravis 45% and epilepsy 31%. The differences are not statistically significant. There was no significant difference in the numbers and locations of bands between the various diagnostic groups and the controls. The overall incidence of immunoreactivity corresponding to the high molecular weight subunit of neurofilaments was only 6%, thus not confirming a previously reported incidence of 95%. The similarity between the diagnostic and the control sera suggests that caution should be exerted in interpreting the pathogenic significance of anti-CNS immunoreactive banding on Western blots.